Compositional Argument Selection in N+V Qualia Pairs within the Discourse of Cooking: A Corpus-based Study - Palma Gutiérrez, Macarena (Miscelánea: A Journal of English and American Studies, 2025)
This paper aims to analyse the compositional argument selection process represented by different syntactic alternations within the specialised domain of cooking, thus contributing to the characterisation of this specialised discourse. The syntactic alternations studied include canonical actives, passives, causative/inchoative alternations, middles and Instrument-subject alternations. These constructions allow the incorporation of cooking verbs (Levin 1993) and denote divergent argument structure realisations. As indicated here through compositional analysis, the constructions contain distinctive N+V qualia pairs. As in Pustejovsky (1991, 1995), this paper follows a lexico-semantic approach and applies a corpus-based methodology to examine and compare over 8,300 contextualised examples from two corpora (a specialised corpus on cooking and a general corpus) using the Sketch Engine corpus tool. The results show that the syntactic alternations examined follow related but distinctive underlying patterns in semantic composition, and thus are construed with N+V qualia pairs that characterise the specialised discourse of cooking.
Keywords: argument selection; compositional analysis; syntactic alternations; discourse of cooking; qualia pairs